تعزيز قدرة الطلاب في السنة الأولى على بناء الجمل البسيطة باستخدام تقويم مبتكر قائم على القوالب: دراسة في المدارس الدينية بمنطقة ساباك برنام، ولاية سيلانجور: Enhancing First-Year Students’ Ability to Construct Simple Sentences Using an Innovative Template-Based Assessment: A Study in Religious Schools in the Sabak Bernam District, Selangor State - Abd Rani, Fatimah Alzahrah (SIBAWAYH Arabic Language and Education, 2024)
يهدف هذا البحث إلى استكشاف فاعلية استخدام تقويم القوالب كابتكار تعليمي لدعم طلاب السنة الأولى في المدارس الثانوية الدينية بمنطقة ساباك برنام، ولاية سيلانجور، في بناء الجمل البسيطة باللغة العربية. تنبع أهمية هذه الدراسة من ملاحظة ضعف الطلاب في تكوين الجمل الصحيحة، مما يؤثر سلبًا على مهاراتهم في الكتابة والتحدث، ويُعزى ذلك إلى صعوبة استخدام القواعد النحوية بشكل سليم. لذلك، تم تطوير تقويم القوالب كأداة تعليمية مبتكرة، توفر للطلاب نماذج جاهزة تساعدهم على فهم التركيب اللغوي بشكل أفضل وبناء الجمل بدقة. شملت الدراسة عينة مكونة من 22 طالبًا، حيث تم تطبيق تقويم القوالب خلال دروس اللغة العربية باستخدام منهج البحث التجريبي، متضمّنًا اختبارات قبلية وبعدية، والملاحظة المباشرة، بالإضافة إلى مقابلات مع المعلمين لتقييم فعالية الابتكار. أظهرت النتائج تحسنًا ملحوظًا في قدرة الطلاب على بناء الجمل البسيطة، إذ كشفت الاختبارات البعدية عن تقليص الأخطاء النحوية بنسبة 40% مقارنة بالاختبارات القبلية. كما أظهرت ملاحظات المعلمين زيادة في دافعية الطلاب للتعلم وثقتهم في بناء الجمل، مما يعزز تفاعلهم في الصفوف الدراسية. وأكدت الدراسة أن الابتكار يسهم في جعل عملية التعلم أكثر سلاسة وجاذبية للطلاب، مما يساعدهم على تجاوز الصعوبات اللغوية. توصي الدراسة باستخدام تقويم القوالب كأداة فعالة في تحسين تعلم اللغة العربية في المراحل الدراسية الأولى، إلى جانب توفير تدريبات كتابية مستمرة وتقييمات دورية لتعزيز مستوى الطلاب وضمان تقدمهم المستدام. This study aims to explore the effectiveness of using template-based assessment as an educational innovation to support first-year students in religious secondary schools in the Sabak Bernam district, Selangor, in constructing simple sentences in Arabic. The significance of this study stems from the observation of students’ weaknesses in forming correct sentences, which negatively impacts their writing and speaking skills. This is attributed to the difficulty in using grammatical rules correctly. Therefore, the template-based assessment was developed as an innovative educational tool, providing students with ready-made models that help them better understand linguistic structures and construct sentences accurately. The study included a sample of 22 students, where the template-based assessment was applied during Arabic lessons using an experimental research method, which included pre- and post-tests, direct observation, and interviews with teachers to assess the effectiveness of the innovation. The results showed a significant improvement in the students’ ability to construct simple sentences, as post-tests revealed a 40% reduction in grammatical errors compared to pre-tests. Teachers’ observations also indicated an increase in students’ motivation to learn and their confidence in constructing sentences, which enhanced their engagement in classrooms. The study confirmed that the innovation contributes to making the learning process smoother and more engaging for students, helping them overcome linguistic challenges. The study recommends using template-based assessment as an effective tool for improving Arabic language learning in the early academic stages, along with providing continuous written exercises and periodic assessments to enhance students’ levels and ensure their sustainable progress. Keywords: Template-Based Assessment, Sentence Construction, Arabic Language Teaching, Educational Innovation, Religious Secondary Schools, Active Learning, Experimental Research.